Benefit of pain and function after cervical transforaminal epidural steroid injections, an observational study - Goyal, Kush K.; Kristoff, Tyler J.; Sinopoli, Jacob T.; Abbott, Matthew; Thompson, Nicolas R.; Koech, Hilary; Rabah, Nicholas (Interventional Pain Medicine (Online), 2023)
To evaluate the improvement of pain and function after cervical transforaminal epidural steroid injections (CTFESI) for radicular pain. This is a retrospective observational study of patients receiving fluoroscopically-guided cervical transforaminal epidural steroid injections under a single provider at a tertiary referral center from December 2013 to December 2020. Primary outcome measures were Numeric Rating Scale (NRS), patient reported percent of pain relief, the Patient Health Questionnaire, the Patient Reported Outcome Measurement Information System (PROMIS) Global Health Physical and Mental Health score, and the Pain Disability Questionnaire. A total of 219 individual patients underwent 261 CTFESI and were included in the analyses. The average subject age was 51.9 years (SD = 11.3) and 50.9 % were male. Following the intervention, average pain relief by NRS at 3 months, 6 months, 1 year, and 2 years was −4.07, −3.82, −4.20, and −4.45, respectively. The average functional improvement with PROMIS-GH physical at 3-months, 6-months, 1- year, and 2-years was 2.23, 2.35, 3.15, and 3.29, respectively. Our results suggest that patients with cervical radiculopathy report significant pain relief and functional improvement following CTFESI. They can also report clinically important improvement in their health-related quality of life.